Emotion felt by the listener and expressed by the music: literature review and theoretical perspectives - Schubert, Emery (Frontiers in Psychology, 2013)
In his seminal paper, Gabrielsson (2002) distinguishes between emotion felt by the listener, here: ‘internal locus of emotion’ (IL), and the emotion the music is expressing, here: 'external locus emotion' (EL). This paper tabulates 16 such publications published in the decade 2003-2012 consisting of 19 studies/experiments and provides some theoretical perspectives. The key findings were that (1) IL ratings was frequently rated statistically the same or lower than the corresponding EL rating (e.g. lower felt happiness rating compared to the apparent happiness of the music), and that (2) self-select and preferred music had a smaller gap across the emotion loci than experimenter selected and disliked music. These key findings were explained by an ‘inhibited’ emotional contagion mechanism, where the otherwise matching felt emotion may have been attenuated by some other factor such as social context. Matching between EL and IL for loved and self-selected pieces was explained by the activation of ‘contagion’ circuits. Physiological arousal, personality and age, as well as musical features (tempo, mode, putative emotions) were observed to influence perceived and felt emotion distinctions. A variety of data collection formats were identified, but mostly using continuous rating scales. In conclusion, a more systematic use of terminology appears desirable with respect to theory-building. Whether two broad categories, namely matched and unmatched, are sufficient to capture the relationships between EL and IL, instead of four categories as suggested by Gabrielsson, is subject to future research.